Negative Parenting Styles in the Second Anime Adaptation of Fruits Basket the Series (2019 - 2021) - Vania Valencia; Setefanus Suprajitno (Institute of Research and Community Outreach - Petra Christian University, 2024)
This paper explores the negative parenting styles employed in the second anime series adaptation of Fruits Basket (2019 - 2021) and the effects on the children, focusing on Ren Sohma, Akito Sohma’s mother, and Isuzu Sohma’s parents as well as the two children. The main theory in this analysis is the parenting styles theory by Diana Baumrind, Eleanor Maccoby, and John Martin. While Ren Sohma’s extreme competitiveness, abuse, and neglect resulted in Akito's emotional hunger, violent tendencies, and rebellion, Isuzu’s parents’ superficial care, abuse, and abandonment led to Isuzu’s low self-worth and self-isolation. This study proves that although both children suffer from authoritarian and neglectful parenting, the different methods that their parents employ lead to different results. Thus, this analysis highlights the long-lasting effects of the negative parenting styles and the varying impacts they have on children.